2017
DOI: 10.1515/adms-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

Increasing of the Mechanical Properties of Friction Stir Welded Joints of 6061 Aluminum Alloy by Introducing Alumina Particles

Abstract: The main aim of this investigation is to produce a welding joint of higher strength than that of base metals. Composite welded joints were produced by friction stir welding process. 6061 aluminum alloy was used as a base metal and alumina particles added to welding zone to form metal matrix composites. The volume fraction of alumina particles incorporated in this study were 2, 4, 6, 8 and 10 vol% were added on both sides of welding line. Also, the alumina particles were pre-mixed with magnesium particles prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Based on the principles of the mechanical metallurgy, the strength of the texture is directly dependent on the characteristics of the grain-boundary network (morphology, density, and distribution) [55][56][57]. Furthermore, the grain size distribution and precipitation of secondary phase are also important microstructural features for controlling the mechanical properties during dynamic Recrystallisation [58][59][60].…”
Section: Ebsd General Texture Evaluationmentioning
confidence: 99%
“…Based on the principles of the mechanical metallurgy, the strength of the texture is directly dependent on the characteristics of the grain-boundary network (morphology, density, and distribution) [55][56][57]. Furthermore, the grain size distribution and precipitation of secondary phase are also important microstructural features for controlling the mechanical properties during dynamic Recrystallisation [58][59][60].…”
Section: Ebsd General Texture Evaluationmentioning
confidence: 99%
“…This may be due to the short peening time, which was in this case 1 min. 4. Based on the test results, it was found that there is a strong correlation between stresses in the FSW welded joint and the force at which the sample is destroyed.…”
Section: Discussionmentioning
confidence: 98%
“…During FSW method, the material does not melting and the joints is free of typical defects arising in the solidification process, such as precipitation, segregation or gas porosity as is the case with remelting processes. This method can be used to join the materials which are difficult to join using conventional welding [3] such as aluminum alloys [4] copper [5], magnesium alloy [6,7], steels [8] or even dissimilar materials [9,10]. The resulting weld has an equiaxial shape and its grains reach a size of 1-10 µm.…”
Section: Introductionmentioning
confidence: 99%
“…It is also concluded that lower welding speed and higher amount of heat input per unit length of the joint help properly consolidate the plasticized material in the nugget zone. On the contrary, with further increase in welding speed to 30 mm min −1 and 35 mm min −1 , the reduction in tensile and impact strength is observed [27,28]. Improper consolidation of plasticized material and interlayer particles is the reason for low tensile and impact strength.…”
Section: Effect Of Welding Speedmentioning
confidence: 97%